Book Review: Miranda Márquez, Gonzalo: A journey through Chinese culture and language - Mironesko, Alexandra Magdalena (Sinología hispánica. China Studies Review, 2022)
Book Review: Miranda Márquez, Gonzalo: A journey through Chinese culture and language